3D-QSAR, molecular docking and dynamics simulation of difluorophenol pyridine derivatives as RSK2 inhibitor - Muhammad Arba, Hamzah Azali, Sabarudin Ombe, Alrum Armid, Ida Usman (Journal of Applied Pharmaceutical Science, 2019)
Given the increasing role of P90 Ribosomal S6 Kinase 2 (RSK2) as an anticancer drug target, we performed 3D-Quantitative structure–activity relationship, including comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) on difluorophenol pyridine derivatives as the inhibitor of RSK2. CoMFA model with q2 of 0.597 and R2 of 0.993, while CoMSIA model with q2 of 0.563 and R2 of 0.993, were obtained. The predictive ability of both models was assured using a test set compound with R2pred values of 0.996 each. Using the validated models, novel compound was proposed and its interaction with RSK2 was investigated employing molecular docking and molecular dynamics simulation of 50 ns. Furthermore, molecular-mechanics Poisson–Boltzmann surface area calculation was performed. The result showed that the newly designed compound has a comparable binding free energy with the known RSK2 inhibitor, indicating its potential as a new RSK2 inhibitor.
Keywords: 3D-QSAR, CoMFA, CoMSIA, docking, difluorophenol pyridine.